Integrated pest management module for thrips, Pseudodendrothrips mori in mulberry under Tamil Nadu climatic condition - Geetha, T; Mahalingam, C A; Murugan, N (Indian Journal of Plant Protection, 2020)
The quality of mulberry leaves plays a vital role in the nutritive requirement of silkworm (Bombyx mori L.), Thrips Pseudodendrothrips mori is a serious pest of mulberry causing quality and quantity losses in mulberry. The monitoring and management of thrips is difficult because of its size, short life duration, high survival rate and effective coverage with insecticides could be hampered by canopy density. Owing to these factors, the availability of management package for mulberry thrips is stumpy. Hence, pest management in mulberry ecosystem with an integrated pest management (IPM) approach remained a significant issue. The present study revealed that the treatment consisting of, 100 per cent NPK + 1.5 per cent K (spray) + intercrop French bean + YST + Neem oil (2 sprays) + Chrysoperla (T6) and 100 per cent NP + 150 per cent K + intercrop French bean + YST + Neem oil (2 sprays) + Chrysoperla (T5) were found to be effective in the management of thrips in mulberry